THE GROWTH INHIBITION OF MARINE BIOFILM-FORMING BACTERIA BY THE CRUDE EXTRACT OF SOFT CORAL Sinularia sp. - Ocky Karna Radjasa; A. Sabdono; Suharsono . (JOURNAL OF COASTAL DEVELOPMENT, 1999)
Marine biofouling has been recognized as a big problem faced by marine technology, and has caused huge economic losses to marine industries. Until recently, marine biofouling has been controlled by the use of metal-based coating which has become another problem because of their negative impacts on marine environments. Soft corals have been known to produce secondary metabolites, some of which may inhibit the fouling processes. The objective of this research was to examine the antimicrobial properties of soft coral Sinularia sp against marine biofilm-forming bacteria The results showed that the soft coral tissues of Sinularia sp. had the antibacterial potency. The crude extracts of Sinularia sp affected significantly on the growth of bacteria tested. The optimal concentration of crude extracts needed to inhibit the growth of bacteria was 150 µg/ml. There were no significantly different among bacteria isolated from fiber, wood and iron steel on diameter of inhibitory zone of the bacterial growth. It is concluded thet the search of bioactive substances produced by soft corals is great possibility to find alternatives for metal-based coatings. Yet, a series of researchs must be undertaken in order to find the secondary metabolites which may be used as antifoulant.